Personality and education profiles of emergency rescuer - Witold Pawłowski; Dorota Lasota; Krzysztof Goniewicz; Mariusz Goniewicz; Patrycja Misztal-Okońska (Kazimierz Wielki University, 2018)
Education of medical emergency rescuers is a hard task and very responsible. The scope of knowledge, which must be adopted during the education by future medical rescuers in view of specificity of profession is wide and miscellaneous. From manners of education and forming of personality of medical rescuer will be depend health and life of victims of case and catastrophes. This article compares the personality characteristics identified by the rescuer medical students toward medical emergency, Medical University of Lublin psycho-physicals with the requirements specific to the profession set out in regulations and standards of training for medical professional rescuers. It also means the development of communication skills and personality of the future emergency rescuers at the Medical University of Lublin.